STEREOTYPICAL IMAGES AND ENEMY PERCEPTIONS IN THE TURKISH NATIONALIST MAGAZINES (1960-1970S) (Journal of Oriental Studies, 2023)
The article examines the theoretical formation of the image of the "enemy", the toolkit necessary for spreading and rooting among social groups. Anti-propaganda tricks and methods to prevent the spread of communism during the "red terror" in Turkey in the 1960-1970s are presented. The most effective means of spreading hatred towards "internal" and "external" enemies and justifying the fight against them, namely the dehumanized depictions and caricatures of the "enemy" character, are being examined in detail.
Keywords: enemy; stereotype; identity; manipulation; caricatures; communist; "red terror"